PERAN MEDIA PEMBELAJARAN DIGITAL DALAM MODUL AJAR KURIKULUM MERDEKA TERHADAP KETERLIBATAN AKTIF SISWA SEKOLAH DASAR: STUDI PUSTAKA - Istikhomah; Hussuludin, Muhammad; Islaminur, Alpina; Salamah, Siti; Suryandari, Meity (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of digital learning media in teaching modules within the Merdeka Curriculum on the active engagement of elementary school students. The research employs a literature review method by examining various scientific sources, including journals, books, and relevant previous studies. Data were collected through documentation techniques and analyzed qualitatively using a descriptive-analytical approach. The findings indicate that digital learning media play a significant role in enhancing the quality of the learning process, particularly in promoting students’ active engagement. The integration of digital media into teaching modules in the Merdeka Curriculum enables more interactive, contextual, and student-centered learning. Furthermore, the use of digital media can increase students’ motivation, participation, and conceptual understanding. However, the effectiveness of digital media utilization depends largely on teachers’ readiness to design structured and innovative teaching modules. Therefore, it is essential to develop teachers’ competencies in optimally integrating digital media into the learning process.